Frequency of Intra-Abdominal Abscess Formation in Perforated Appendix after Laparoscopic Appendectomy - Asghar, Ayesha; Mujahid, Muhammad Dilawaiz; Asghar, Alia (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the frequency of post-operative intra-abdominal abscess (IAA) formation following laparoscopic appendectomy in cases of perforated appendicitis. Study Settings: The study was conducted in the Surgical Department of Allied Hospital Faisalabad and Faisalabad Medical University. Duration of Study: This descriptive study was carried out over six months following approval of the synopsis. Data Collection: A total of 160 patients aged 18–75 years, diagnosed with perforated appendicitis and managed with laparoscopic appendectomy, were included through non-probability consecutive sampling. Patients with prior abdominal surgery, uncontrolled diabetes, pregnancy, or malignancy were excluded. Post-operative IAAs were identified through clinical symptoms, laboratory findings, and ultrasonography within one week of surgery. Data were analyzed using SPSS version 25, with stratification for age, gender, and BMI. Chi-square tests were applied, and a p-value ≤ 0.05 was considered statistically significant. Results: The mean age of participants was 41.3 ± 13.7 years, with a majority (58.8%) aged 18–50 years. Male patients constituted 62.5% of the sample, and 65.6% had a BMI >25. The overall frequency of post-operative IAAs was 9.4%. Stratified analysis showed no significant differences in IAA rates based on age (p = 0.228), gender (p = 0.183), or BMI (p = 0.509). Conclusion: Laparoscopic appendectomy is associated with a low frequency of IAAs in cases of perforated appendicitis, regardless of age, gender, or BMI. These findings support its adoption as the standard of care in resource-limited settings like Pakistan, offering improved outcomes and reduced healthcare burden.